Characterization of phosphate wastes of Djebel Onk mining complex for a sustainable environmental management - Salhi, Rachid; Nettour, Djamel; Chettibi, Mohamed; Gherbi, Cherif; Benselhoub, Aissa; Bellucci, Stefano (Technology audit and production reserves, 2023)
The objects of the research are phosphate ore rejections – industrial waste resulting from the treatment of phosphate ore by different processes (particle size separation, calcination, physicochemical process, electrostatically process, etc.). These discharges are generally stored in specially constructed sedimentation ponds. However, its storage for a long period leads to serious environmental problems because they contain heavy and radioactive metals that affect nearby communities. They contaminate groundwater and surface water through the infiltration of caustic solution laden with rare metals. To remedy these environmental disasters and manage these concerns, it is necessary to upgrade the discharges from the Djebel Onk complex and give an added value to the national economy. The start-up of the Djebel El Onk phosphate complex, in the province of Tebessa was in 1965, since that date, all the waste resulting from the beneficiation process has been dumped in the valley adjacent to the complex without any treatment or recycling, it should be noted that the Djebel Onk phosphate complex generates huge quantities of phosphate sludge (more than 4000 tons per day). This waste is relatively rich in useful substance. The results of chemical analyzes reveal that these sludge’s contain around 20.2 % of phosphate (P2O5) with the presence of different heavy metals such as Uranium, Cadmium, Zinc, Copper, and Arsenic etc. Those metals threaten life of local residents and affects vegetation, livestock in nearby populated areas. However, this work systematically reviews the mineralogical and chemical characterization of the phosphate sludge rejected by the Djebel Onk treatment complex to develop a suitable method for their revaluation. In our work, in this viable environmental perspective, we try to highlight the use of wastes as an alternative raw material in building materials. The impact of heavy metals on the environment and health is determined by the chemical species, concentration, bioavailability and transport through food chains, unless they are released into nature due to the consequences harm they create. Certain elements, such as mercury, lead, cadmium, zinc, copper, etc., have no function in maintaining body balance and are immediately dangerous.